2010
DOI: 10.3109/09513591003767948
|View full text |Cite
|
Sign up to set email alerts
|

Urogenital disorders associated with oestrogen deficiency: the role of promestriene as topical oestrogen therapy

Abstract: Urogenital disorders associated with oestrogen deficiency affect many women throughout menopausal transition. Symptoms such as vaginal dryness, burning, pruritus, dyspareunia, urinary tract urgency/frequency and incontinence have a significant impact on the individual's quality of life. For younger and healthy menopausal women, systemic oestrogen replacement may improve both vasomotor and urogenital symptoms and will be the treatment of choice. However, a proportion of women on systemic therapy still experienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 19 publications
1
13
0
1
Order By: Relevance
“…The effects on the individual can be serious when they markedly impact their sexuality, redefining their feminine role and ultimately negatively impacting their physical and mental well being. 40 So far, VVA treatment with estrogens has essentially been limited to the most superficial or epithelial layer, which is largely responsible for pain at sexual activity or dyspareunia. Contraction of the introitus, and shortening and narrowing of the vaginal canal are not related to the superficial layer, but rather depend upon loss of collagen and muscular components in the lamina propria and muscularis layers, respectively.…”
Section: Labrie Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…The effects on the individual can be serious when they markedly impact their sexuality, redefining their feminine role and ultimately negatively impacting their physical and mental well being. 40 So far, VVA treatment with estrogens has essentially been limited to the most superficial or epithelial layer, which is largely responsible for pain at sexual activity or dyspareunia. Contraction of the introitus, and shortening and narrowing of the vaginal canal are not related to the superficial layer, but rather depend upon loss of collagen and muscular components in the lamina propria and muscularis layers, respectively.…”
Section: Labrie Et Almentioning
confidence: 99%
“…36,37 VVA has been reported in more than 60% of women after the fourth year of menopause. [38][39][40] The intracellular transformation of DHEA into estrogens is apparently responsible for the maturation of the parabasal cells which are transformed into intermediate and then into superficial cells. 5 DHEA has also been shown in preclinical studies to induce mucification of the epithelium or superficial layer of the vaginal mucosa while increasing the density of the collagen fibers in the second layer (lamina propria) and stimulating the muscular third layer.…”
Section: Labrie Et Almentioning
confidence: 99%
“…According to Santos and Clissold [35] it has two important attributes: 1) Firstly, it is very poorly absorbed by the vagina and does not affect systemic hormone levels or estrogen activity. The minimal (51%) absorption of Promestriene mostly occurs at the very beginning of the treatment, as a consequence of the atrophic vaginal mucosa being thin and having several micro-fissures.…”
Section: Discussionmentioning
confidence: 99%
“…In several small open-label studies, it was shown to significantly improve vulvovaginal trophicity and related symptoms in both naturally and surgically menopausal women with minimal absorption [14]. A study of 17 women treated for gynaecological cancer given promestriene 10 mg vaginal suppository for a month found that levels of circulating estrone sulfate were not significantly affected overall, but a wide range was noted pre and post treatment in individual patients [15].…”
Section: Promestrienementioning
confidence: 99%